“Grid”-Less Power Systems: A Vision for Future Structure of Power Networks - Meghdad Fazeli (IEEE Access, 2020)
This paper proposes a new paradigm in the structure of power systems to facilitate the large scale move to renewables-based distributed generation necessary to help decarbonize the current electricity networks. Since the design of the incumbent power system topologies is to control large synchronous generators, critical control metrics degrade as the penetration of converter-based units increases. Specifically, the reduction in short circuit level, phase angle movement, and rate of change of frequency limit the wider adoption of converter-based units. This paper proposes structural changes and control that inherently solve such critical performance issues through physically decoupling all synchronous generators from the network. A set of back-to-back AC/DC/AC converters controlled by a universal virtual synchronous machine-based control algorithm, introduced in the paper, allows the repurposing of existing plant to enable the integration of more converter-based units. Despite being physically disconnected, this new structure/control still benefits from inertial capacities of synchronous generators to suppress the oscillations caused by disturbances. Moreover, the method enables further exploitation of synchronous generators as energy storage mechanisms. PSCAD/EMTDC simulations demonstrate the advantages of the proposed structure and control system in different normal and abnormal scenarios.